Inkubator ''Entrepreneur Passion'' Sebagai Wahana Generator Semangat dan Ketrampilan Berwirausaha Pelajar Menengah - Rahmi, Vembri Aulia (Universitas Muhammadiyah Gresik, 2019)
Actually, disruption era showed the birth of a new spirit of national progress. However, it is evident that not entirely a positive influence and still high unemployment. From the beginning people must be able to educate themselves as creative and innovative people. It is not easy to create entrepreneurial characters, through entrepreneurship development in schools, entrepreneurial mentality is instilled. Business incubators has been widely applied to universities and has not been widely applied in schools. This study aims to explain how the implementation of the incubator as a vehicle to foster entrepreneurial character in middle school students. Using a descriptive qualitative research method with in-depth interviews with the incubator program presenters and the results of polls of several participants, it can be seen that the findings of this study demonstrate entrepreneurship in